Countermeasures for timing-based side-channel attacks against shared, modern computing hardware. (10th April 2019) - Montasari, Reza; Hill, Richard; Hosseinian-Far, Amin; Montaseri, Farshad
There are several vulnerabilities in computing systems hardware that can be exploited by attackers to carry out devastating microarchitectural timing-based side-channel attacks against these systems and as a result compromise the security of the users of such systems. By exploiting microarchitectural resources, adversaries can potentially launch different variants of timing attacks, for instance, to leak sensitive information through timing. In view of these security threats against computing hardware, in a recent study, titled 'Are timing-based side-channel attacks feasible in shared, modern computing hardware?', currently undergoing the review process, we presented and analysed several such attacks. This extended study proceeds to build upon our recent study in question. To this end, we analyse the existing countermeasures against timing attacks and propose new strategies in dealing with such attacks.